Direct fabrication of glass microfluidic channel using CO2 laser - Norfazilasari, Yasman; Raja Murfiqah, Raja Mohd Fouzy; Mohd Zairulnizam, Mohd Zawawi (Elsevier Ltd, 2023)
The design and development of small and compact devices with numerous new functions and vast benefits to the society is steadily receiving global attention. These sophisticated small devices require the production of accurate and intricate micro and nano-scale patterns with different three-dimensional (3D) shapes, sizes, and aspect ratios. Microfluidic device or so-called lab-on-a-chip (LOC) is one example of a highly sensitive and compact integrated device capable of detecting multiple analytes, usually used as a diagnostic device. In this study, we demonstrate the feasibility study for direct fabrication of microfluidic channel on transparent optical glass substrate via CO2 direct laser structuring. A custom-built direct laser structuring setup mainly consist of a commercial continuous type of CO2 laser source and glass preheating apparatus is utilized. First, the relationship between the process parameters, mainly the laser scanning speed, number of lasers passes and initial glass preheating temperature to the formation of microchannel of different width, height and shape were established. Then, the form accuracy and the morphology of the microchannels were characterized using laser scanning confocal microscope (LSCM) and surface profiler. Overall, the result reveals that the combination of higher laser power, lower scanning speed and higher number of laser passes promotes the increase of both the width and height of the microchannel. Preheating was found to be necessary for the glass used in this study in avoiding either micro-cracks or bulk glass cracking. Based on the relationship between laser scanning speed and the number of laser passes, a prototype of a microfluidic channel with average width and height of about 235 ± 10 µm and 6 ± 0.3 µm, respectively was successfully fabricated. This study opens an opportunity for further improvement and research for fabrication of crack-free and smooth microfluidic channels using low-cost CO2 laser structuring setup.